Transport-defective Escherichia coli ecf mutant permeable to protons and nucleotides. - Tomchika, K I (1978)
This paper describes a third type of transport-defective ecf mutant of Escherichia coli which is altered in membrane proton permeability. Mutants of this class also excrete ATP and other nucleotides and form filament-like cells. This lesion requires cell growth at the nonpermissive temperature.